Analisis Produktivitas Pekerja Menggunakan Metode Work Sampling di Toko XYZ - Putri Amalia Muntaha; Dene Herwanto; Mohammad Rifany Asyidikiah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
The current industrial era is getting stricter in terms of job search criteria, so workers must improve their consistency and ability to understand the work system well. The work system is a combination of work elements that interact and are integrated effectively and productively to achieve the desired goals. Toko XYZ is a micro, small and medium enterprise (MSME) which is engaged in selling basic commodities. The problem that occurs in the shop is that it has not been able to determine the standard time, standard production, and the calculation of the workload experienced by workers. The objectives to be achieved in this study are to determine the level of productivity of shift 1 workers by measuring work sampling, calculating the standard time experienced by the three workers, and determining the number of sales in shift 1. The results obtained from measurements using the work sampling method are Worker 1 gains time more productive with a value of 8.76 hours compared to Worker 2 and Worker 3 with 8.72 hours and 8.09 hours, respectively. The worker with the highest workload value is worker 3 with a value of 88.09%. Suggestions and solutions that can be given are by motivating workers to be more active at work and increasing other supporting facilities, so as to increase worker productivity and reduce non-productive activities of workers.